Molecular identification and functional characterization of two glycosyltransferases genes from Fallopia multiflora - Cai, Qizhong; Liu, Changzheng; Liu, Lu; Ge, Yuewei; Cheng, Xuanxuan; Luo, Bi; Zhou, Liangyun; Yang, Quan (Frontiers in Plant Science, 2022)
The traditional Chinese medicine plant Fallopia multiflora (Thunb.) Harald. contains various pharmacodynamically active glycosides, such as stilbene glycosides, anthraquinone (AQ) glycosides, and flavonoid glycosides. Glycosylation is an important reaction in plant metabolism that is generally completed by glycosyltransferase in the last step of the secondary metabolite biosynthesis pathway, and it can improve the beneficial properties of many natural products. In this study, based on the transcriptome data of F. multiflora, we cloned two Uridine-diphosphate glycosyltransferases (UGTs) from the cDNA of F. multiflora (FmUGT1 and FmUGT2). Their full-length sequences were 1602 and 1449 bp, encoding 533 and 482 amino acids, respectively. In vitro enzymatic reaction results showed that FmUGT1 and FmUGT2 were promiscuous and could catalyze the glycosylation of 12 compounds, including stilbenes, anthraquinones, flavonoids, phloretin, and curcumin, and we also obtained and structurally identified 13 glycosylated products from both of them. Further experiments on the in vivo function of FmUGT1 and FmUGT2 showed that 2, 3, 5, 4'- tetrahydroxy stilbene-2-O-β-D-glucoside (THSG) content in hairy roots was elevated significantly when FmUGT1 and FmUGT2 were overexpressed and decreased accordingly in the RNA interference (RNAi) groups. These results indicate that FmUGT1 and FmUGT2 were able to glycosylate a total of 12 structurally diverse types of acceptors and to generate O-glycosides. In addition, FmUGT1 and FmUGT2 efficiently catalyzed the biosynthesis of THSG, and promoted the production of AQs in transgenic hairy roots.